EXPORTS AS A TRIGGER OF ECONOMIC GROWTH OF THE REPUBLIC OF SERBIA - Ignjatović, Jelena; Kisin, Jovana; Brajković, Mileta (Poslovna ekonomija, 2021)
In recent years, Serbian exports, accompanied by the inflow of foreign direct investment, have improved significantly, resulting in stronger economic growth. However, despite the positive predictions of the European Commission for further growth of exports and the jump of economic growth in Serbia, our economy is facing serious consequences caused by the COVID-19 pandemic, which is affecting the whole world. The paper aims to present the current macroeconomic picture of the Republic of Serbia through the analysis of import and export policy, the volume of foreign trade and their impact on economic growth. In relation to the set goals, the paper is divided into four thematic units, with conclusions and possible recommendations at the end. Special emphasis was placed on exports, its development opportunities and improving competitiveness, as well as the presentation of recommendations within the Serbia’s New Growth Agenda. The subject of this paper is based on theoretical data analysis, through descriptive and comparative methods as well as the synthesis of theoretical and empirical facts. For this research the primary empirical data were collected from various relevant sources.
Keywords: export, trigger, foreign trade, economic growth, Serbia